O ser feminino: comparações e diferenças em obras de Florbela Espanca e Conceição Evaristo - SANTANA, Caroline da Silva (2024)
The analysis in this text discusses the evolution of female representation in literature over different centuries, highlighting the changes in the process of female authorship. The aim is to talk about the female being in literary works, highlighting the image of women as its main object of study. This work is a bibliographical study in the field of literature, which was carried out in a qualitative way, studying the representation of women in literature from the 19th to the 21st centuries, through the sonnets "Mulher I" and "Mulher II" by Florbela Espanca and "Eu-Mulher" by Conceição Evaristo. The entire historical process and analysis of the works was shown, with the aim of exposing the changes and connections that have occurred over the years in the way they are presented in society, removing the image of beauty and showing the real thing about them. To prove this, we used some scholars who talk about feminism and the image of women in society and in literature. Therefore, reading this production will lead readers to reflect on the way women's feelings were described, which only became more evident with the arrival of female authors who wrote about the true identity of real women.